COMPUTERIZED ACCEPTANCE OF ITS EMPLOYEES IN PT.MARGA GRAHA USING DATABASE III - Cahya Widiastuti; Drs.Eko Hadiyanto (Jurnal Sistem Informasi, 1997)
Usage of computers as aids in recruitment of employees in this new Penta GrahaPT.Marga at an early stage or a trial, for it still felt the need for improvements to theresults obtained more perfect, but at least this program can assist in collecting anddisplaying re- existing data and computer information, so that at a time of need can befound quickly.The use of computerized recruitment is very practical and easy to use because the liveview and choose menus that are already available on the program and the commandhas been using the Indonesian language that is understandable.